Penguatan Konsep Pendidikan Politik Generasi Muda Pemilih Pemula Jambi Melalui Kuliah Umum Pendidikan Politik - Hendra; Priazki Hajri; Nurmalia Dewi; Dona Sariani; Firdiawan Ekaputra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The service activity is motivated by the fact that the political participation of the younger generation is still lacking and this needs to be remembered considering the very large number of segments in the 2024 election. This activity aims to provide insight into political education to the younger generation to increase awareness and increase the political participation of the younger generation and so that it is not easy influencing hoax news that developed in the year leading up to the election. Activities were carried out in the form of offline and dare public lectures via YouTube and Zoommeeting on September 18 2023. Activities were carried out in two stages, namely planning and implementation. Activities can broaden students' insight as young millennials and new voters regarding politics are increasing, thus increasing their awareness in politics. Public lectures also strengthen the political understanding of the younger generation so that they are not easily influenced by hoax news related to certain issues by first checking information about the issue. Through this activity, it is hoped that it can increase the political understanding and awareness of the younger generation. Kegiatan pengabdian dilatarbelakangi oleh fakta bahwa partisipasi politik generasi muda masih kurang dan perlu ditingkatkan mengingat jumlah segmentasi ini yang sangat besar pada pemilu 2024. Kegiatan ini bertujuan untuk memberikan wawasan pendidikan politik kepada generasi muda untuk meningkatkan kesadaran dan meningkatkan partisipasi politik generasi muda serta agar tidak mudah terpengaruh berita hoaks yang berkembang pada tahun menjelang pemilu. Kegiatan dilakukan dalam bentuk kuliah umum secara luring dan daring melalui Youtube dan Zoommeeting pada 18 September 2023. Kegiatan dilakukan dengan dua tahap yakni perencanaan dan pelaksanaan. Kegiatan dapat menambah wawasan mahasiswa sebagai generasi muda milenial dan pemilih pemula terkait politik bertambah sehingga meningkatkan kesadaran mereka dalam berpolitik. Kuliah umum juga memperkuat pemahaman politik generasi muda agar tidak mudah terpengaruh berita hoaks terkait isu-isu tertentu dengan terlebih dahulu melakukan pengecekkan informasi tentang isu tersebut. Melalui kegiatan ini, diharapkan dapat meningkatkan pemahaman dan kesadaran politik generasi muda.